2021
DOI: 10.1002/nop2.1046
|View full text |Cite
|
Sign up to set email alerts
|

Licenced practical nurses' perceptions of their work environments and their intention to stay: A cross‐sectional study of four practice settings

Abstract: These factors make retaining nurses increasingly important for employers. Previous research has shown that nursing turnover may be costly to an organization due to replacing employees, reduced productivity and negative effects in the organizational culture that can affect the organization's ability to give safe nursing care (Hayes et al., 2012). It is essential for nurse leaders to understand factors that enhance retention, including nurses' work environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…However, the results of the present study were contradicted by the findings of a study conducted by Almuhsen et al [ 24 ], who reported that the highest mean score among the five subscales was for staffing and resource adequacy. In addition, the results of the current study were incongruent with those of Phillips et al [ 20 ], who found a high level of agreement for nurse staffing and resource-contributing variables among nurses in Alberta, Canada.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the results of the present study were contradicted by the findings of a study conducted by Almuhsen et al [ 24 ], who reported that the highest mean score among the five subscales was for staffing and resource adequacy. In addition, the results of the current study were incongruent with those of Phillips et al [ 20 ], who found a high level of agreement for nurse staffing and resource-contributing variables among nurses in Alberta, Canada.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings provide further validation of the results of a few national studies [17][18] and another international study in Brazil [19]. In contrast, other studies from Canada [20] and Korea [21] found that nurses rated their practice environments as mixed. On the other hand, a study conducted by Brofidi et al [16] at five public hospitals in Greece showed that nurses assessed all five hospitals as unfavorable nursing practice environments.…”
Section: Discussionsupporting
confidence: 79%
“…The education and role of HCAs in Slovenia is comparable to the role of non-licensed practical nurses. Similarly, Phillips et al [ 35 ] found this group of nursing care providers to have a lower self-assessment of the work environment and lower job satisfaction. Our study also showed HCAs to be less satisfied with their job, career, flexibility of work schedule, opportunities for development, autonomy at work, professional status, salary, educational opportunities, and leave.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips et al. [5] indicate that having adequate access to resources, proper leadership training, and sufficient staffing levels are all beneficial to retaining staff at healthcare organizations. Zaheer et al.…”
Section: Background and Contextmentioning
confidence: 99%
“…Published literature from both the Canadian and international healthcare sectors identified key themes. These included autonomy, equity, mentorships, relationships, support system, strong leadership, diversity, and culture, as well as career and educational development [ 5 , 6 , 8 ].…”
Section: Scope Strategies and Outcomesmentioning
confidence: 99%